The Current State of Robot-Assisted Minimally Invasive Esophagectomy (RAMIE): Outcomes from the Upper GI International Robotic Association (UGIRA) Esophageal Registry - Kooij, Cezanne D; de Jongh, Cas; Kingma, B Feike; van Berge Henegouwen, Mark I; Gisbertz, Suzanne S; Chao, Yin-Kai; Chiu, Philip W; Rouanet, Philippe; Mourregot, Anne; Immanuel, Arul; Mala, Tom; van Boxel, Gijs I; et al. (Annals of surgical oncology, 2025)
BACKGROUND: Robot-assisted minimally invasive esophagectomy (RAMIE) is increasingly adopted in centers worldwide, with ongoing refinements to enhance results. This study aims to assess the current state of RAMIE worldwide and to identify potential areas for improvement. METHODS: This descriptive study analyzed prospective data from esophageal cancer patients who underwent transthoracic RAMIE in Upper GI International Robotic Association (UGIRA) centers. Main endpoints included textbook outcome rate, surgical techniques, and perioperative outcomes. Analyses were performed separately for intrathoracic (Ivor-Lewis) and cervical anastomosis (McKeown), divided into three time cohorts (2016-2018, 2019-2020, 2021-2023). A sensitivity analysis was conducted with cases after the learning curve (> 70 cases). RESULTS: Across 28 UGIRA centers, 2012 Ivor-Lewis and 1180 McKeown procedures were performed. Over the time cohorts, textbook outcome rates were 39%, 48%, and 49% for Ivor-Lewis, and 49%, 63%, and 61% for McKeown procedures, respectively. Fully robotic procedures accounted for 66%, 51%, and 60% of Ivor-Lewis procedures, and 53%, 81%, and 66% of McKeown procedures. Lymph node yield showed 27, 30, and 30 nodes in Ivor-Lewis procedures, and 26, 26, and 34 nodes in McKeown procedures. Furthermore, high mediastinal lymphadenectomy was performed in 65%, 43%, and 37%, and 70%, 48%, and 64% of Ivor-Lewis and McKeown procedures, respectively. Anastomotic leakage rates were 22%, 22%, and 16% in Ivor-Lewis cases, and 14%, 12%, and 11% in McKeown cases. Hospital stay was 13, 14, and 13 days for Ivor-Lewis procedures, and 12, 9, and 11 days for McKeown procedures. In Ivor-Lewis and McKeown, respectively, the sensitivity analysis revealed textbook outcome rates of 43%, 54%, and 51%, and 47%, 64%, and 64%; anastomotic leakage rates of 28%, 18%, and 15%, and 13%, 11%, and 10%; and hospital stay of 11, 12, and 12 days, and 10, 9, and 9 days. CONCLUSIONS: This study demonstrates favorable outcomes over time in achieving textbook outcome after RAMIE. Areas for improvement include a reduction of anastomotic leakage and shortening of hospital stay.
Keywords: Female; Robotic Surgical Procedures; ženské pohlaví; Robot-assisted esophagectomy; Registries; Esophageal cancer; lidé; Esophageal Neoplasms; pooperační komplikace; následné studie; ezofagektomie; Minimally Invasive Surgical Procedures; prognóza; nádory jícnu; Middle Aged; prospektivní studie; Follow-Up Studies; Male; Postoperative Complications; Prospective Studies; Aged; Prognosis; Esophagectomy; lidé středního věku; registrace; senioři; mužské pohlaví; miniinvazivní chirurgické výkony; Minimally invasive esophagectomy; roboticky asistované výkony; Humans